PERAN TIM KESEHATAN DALAM MENDUKUNG PELAKSANAAN PERKEMAHAN ANTAR SATUAN KARYA NASIONAL 2025 - Novia Martin; Zuhriana K. Yusuf (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2026)
The 2025 National Inter-Scout Unit Camp involved participants from various regions and required optimal health service support. Fatigue, minor injuries, common illnesses, and emergency medical conditions were the main challenges in large-scale outdoor activities. This community service aimed to provide basic medical services, first aid, and health education to camp participants through the establishment of a field health team. The activity was carried out on Tuesday, November 4th, 2025 from 07.30–14.00 WITA at Bongohulawa Camping Ground, Limboto. The implementation method was conducted through direct health services including registration, blood pressure and body temperature checks, doctor examination, and medicine administration according to participants’ needs. The health team consisted of lecturers and health workers from the Faculty of Medicine, Universitas Negeri Gorontalo. The results showed that health services were carried out effectively, participants received quick access to basic medical services, and awareness of the importance of early health detection during camp activities increased. The presence of a field hospital also provided a sense of safety for participants and organizers. This activity proves that health team collaboration in field activities can improve the quality of community health services and support the overall success of national events.